PROFIL KONSEP DIRI PESERTA DIDIK BERKEBUTUHAN KHUSUS (Studi Kasus di SMK Negeri 3 Sukabumi) - Mauly Ismadina, - (2021)
Self-concept is a crucial aspect that needs to be had for students with special needs in order for them to be able to participate and adapt to social environment optimally. The research is conducted to descript a self-concept profile and revealed factors that influence self-concept within students with special needs in state 3 Vocational high school Sukabumi. The research is conducted on participant FS using a qualitative approach and case study method. The result shows that participant FS has a positive self-concept in moral and social self-concept aspects. Factors that influence the positive self-concept within the participant is feedback factor obtained from significant others. The implication of the research is a development of guidance and counseling service programs to develop positive self-concept in students with special needs. Keywords: Self-Concept, Student, Students with Special Needs.